2018
DOI: 10.11648/j.jdmp.20180403.11
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Accumulation of Five Main Bioactive Components in the Roots of <i>Salvia miltiorrhiza</i> at Different Growth Stages and Using Different Culture Systems

Abstract: To Growth and accumulation of five main bioactive components in the roots of Salvia miltiorrhiza at different growth stages and using different culture systems. We analyzed growth parameters and the accumulation of selected bioactive components in Salvia miltiorrhiza that was grown in quartz sand-pot (hydroponic culture), soil-pot, and field culture systems at 3 growth stages (flower, root swelling, and mature). The highest bioactive compound concentrations (danshensu (DSS), 0.618 mg·g -1 ; salvianolic acid B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Additionally, cultivars CIM-Jagriti and Subodhak when grown under hydroponics had 7.59 and 7.44 percent, respectively, more bacoside-A when compared to soil grown cultivars. Similar results of enhancement of bioactive compounds in plants grown under hydroponics has been reported by Lu et al (2018) in Salvia miltiorrhiza, Surendran et al (2017) in Mentha spicata, and Pedneault et al (2002) in Achillea millefolium. The reason for the increment of bioactive compounds under hydroponics is -control over the whole process of…”
Section: Resultssupporting
confidence: 86%
“…Additionally, cultivars CIM-Jagriti and Subodhak when grown under hydroponics had 7.59 and 7.44 percent, respectively, more bacoside-A when compared to soil grown cultivars. Similar results of enhancement of bioactive compounds in plants grown under hydroponics has been reported by Lu et al (2018) in Salvia miltiorrhiza, Surendran et al (2017) in Mentha spicata, and Pedneault et al (2002) in Achillea millefolium. The reason for the increment of bioactive compounds under hydroponics is -control over the whole process of…”
Section: Resultssupporting
confidence: 86%
“…However, most of the previous studies used mature roots of S. miltiorrhiza as the plant materials. There are few studies on the temporal evaluation of the root growth and development of S. miltiorrhiza [ 31 ]. Therefore, we chose young roots of S. miltiorrhiza as the research material to explore the initial synthesis of tanshinone.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the taproots underwent rapid and complex development. In previous studies, it was also shown that the root of S. miltiorrhiza , when grown for longer than 60 days, can accumulate a large amount of tanshinone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroponic production, systems in which nutrients are delivered to the plant via liquid solutions in lieu of soil, of medicinal plants is an increasingly attractive solution to quantity and quality issues in the production of marketable phytochemicals. Medicinal plants have been successfully grown in hydroponic culture for harvest of aboveground tissue (Kiferle et al 2011;Prasad et al 2012;Kaul et al 2017;Surendran et al 2017), root and rhizome tissue (Akiyama et al 2017;Lu et al 2018), and multiple tissues simultaneously (Kim et al 2010;Pedneault et al 2014). In situ production of phytochemicals is strongly influenced by temperature, light and nutrient availability, pH, and interaction with soil microorganisms and herbivores (Canter et al 2005), and these factors can be difficult to manage in agricultural fields.…”
Section: Introductionmentioning
confidence: 99%